Lung clearance index and diffusion capacity for CO to detect early functional pulmonary impairment in children with rheumatic diseases - Julia Hildebrandt; Anja Rahn; Anja Kessler; Fabian Speth; Dagmar-Christiane Fischer; Manfred Ballmann (BMC, 2021)
Abstract Background In adults with rheumatic diseases pulmonary complications are relevant contributors to morbidity and mortality. In these patients diffusion capacity for CO (DLCO) is an established method to detect early pulmonary impairment. Pilot studies using DLCO indicate that early functional pulmonary impairment is present even in children with rheumatic disease albeit not detectable by spirometry and without clinical signs of pulmonary disease. Since the lung clearance index (LCI) is also a non-invasive, feasible and established method to detect early functional pulmonary impairment especially in children and because it requires less cooperation (tidal breathing), we compared LCI versus DLCO (forced breathing and breath-holding manoeuvre) in children with rheumatic diseases. Findings Nineteen patients (age 9-17 years) with rheumatic disease and no clinical signs of pulmonary disease successfully completed LCI and DLCO during annual check-up. In 2 patients LCI and DLCO were within physiological limits. By contrast, elevated LCI combined with physiological results for DLCO were seen in 8 patients and in 9 patients both, the LCI and DLCO indicate early functional pulmonary changes. Overall, LCI was more sensitive than DLCO to detect early functional pulmonary impairment (p = 0.0128). Conclusions Our findings suggest that early functional pulmonary impairment is already present in children with rheumatic diseases. LCI is a very feasible and non-invasive alternative for detection of early functional pulmonary impairment in children. It is more sensitive and less cooperation dependent than DLCO. Therefore, we suggest to integrate LCI in routine follow-up of rheumatic diseases in children.